Stereoisomers of Ieodoglucomides A and B: Synthesis and Evaluation of Anticancer Activity - Reddy, Chada Raji; Jithender, Enukonda; Singh, Ashita; Ummanni, Ramesh (Synthesis, 2014)
Asymmetric total synthesis of α-isomers of ieodoglucomides A and B along with their C14-epimers has been achieved starting from d-glucose. The key reactions involved are α-glycosylation and Grubbs olefin cross-metathesis. These stereochemical analogues and their β-isomers (natural products) were screened for their effects on cytotoxicity against various cancer cell lines and it was found that a few analogues are active relative to the natural ieodoglucomides.
Keywords: glycolipids; glycosylation; cross-metathesis; cytotoxicity; stereoisomer